A Clinician's Guide to the Implementation of Point-of-Care Ultrasound (POCUS) in the Outpatient Practice - Joshua Overgaard; Bright P. Thilagar; Mohammed Nadir Bhuiyan (SAGE Publishing, 2024)
Point-of-care ultrasound (POCUS) is a valuable clinical tool used at the patient bedside to rapidly assess a wide variety of symptoms and problems which would otherwise take hours or even days. Though it has become the standard of care in Emergency Medicine and is becoming so in hospital internal medicine, less uptake has been appreciated in the outpatient setting despite reported interest from clinicians practicing there. A number of common barriers have been cited to explain this gap in use, which usually include access to equipment, mentorship, and time. In this review we present a proposed framework for clinicians who have an interest in implementing POCUS in their outpatient practice which we hope can mitigate some of these barriers and provide a more streamlined pathway to their desired goals.